2005
DOI: 10.1152/ajpgi.00046.2005
|View full text |Cite
|
Sign up to set email alerts
|

Lack of pyloric interstitial cells of Cajal explains distinct peristaltic motor patterns in stomach and small intestine

Abstract: The frequency and propagation velocity of distension-induced peristaltic contractions in the antrum and duodenum are distinctly different and depend on activation of intrinsic excitatory motoneurons as well as pacemaker cells, the interstitial cells of Cajal associated with Auerbach's plexus (ICC-AP). Because ICC are critical for coordination of motor activities along the long axis of many regions in the gut, the role of ICC in antroduodenal coordination was investigated. We used immunohistochemistry, electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 55 publications
(54 reference statements)
4
59
2
Order By: Relevance
“…Previously, conventional multiple electrodes have been applied to investigate coordination of motor activity in a rather large distance, e.g. antroduodenal coordination (Wang et al 2005;Lammers et al 2005). Recently, our MEA study successfully demonstrated the propagation of pacemaker potentials generated by an ICC network in a small area (~4 mm 2 ) of the stomach musculature (Nakayama et al 2006).…”
Section: Applications Of Mea In Gut Pacemakersmentioning
confidence: 72%
“…Previously, conventional multiple electrodes have been applied to investigate coordination of motor activity in a rather large distance, e.g. antroduodenal coordination (Wang et al 2005;Lammers et al 2005). Recently, our MEA study successfully demonstrated the propagation of pacemaker potentials generated by an ICC network in a small area (~4 mm 2 ) of the stomach musculature (Nakayama et al 2006).…”
Section: Applications Of Mea In Gut Pacemakersmentioning
confidence: 72%
“…Several authors, Quigley et al (1985), Dinning et al (1999), Hipper and Ehrlein (2001), Malbert (2005) found the motility of the ileocolonic junction mostly synchronized, in pigs 70% of ileal contractions are coordinated with colonic contractions. In contrast, according to Cai and Gabella (1984), Lammers et al (1998), and Wang et al (2005), muscular contractions are not normally propagated from the pyloric end of the stomach to the duodenum.…”
Section: Discussionmentioning
confidence: 90%
“…More recently, Wang et al (2005) discovered a gap in the continuity in the myenteric ICC network at the pyloric sphincter, which is accountable for the break in the propagation of electric slow wave activity from the stomach to the duodenum and for the distinct uncoordinated peristaltic motor patterns of the stomach and the duodenum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in rodent models have suggested the lack of ICC populations in the pylorus allows for distinct antral and duodenal motor activity whereby duodenal distension from deposited gastric contents stimulates aboral duodenal contractions that enable independent contractions at appropriate intervals [7]. Nonetheless, ICC populations are essential for motility, as demonstrated by studies of the contribution of ICC to pyloric stenosis and hypertrophy in pediatric patients [8].…”
Section: Interstitial Cells Of Cajalmentioning
confidence: 99%